PREPARATION OF SENSORS BASED ON Fe OXIDE DOPED WITH Pt FOR DETECTION OF METHANE - Picasso, Gino (2015)
Some sensors based on pure α-Fe2O3 (hematite) and doped with %Pt-loadings (respectto oxide) of 0,1; 0,2 y 0,3% have been prepared by precipitation method for detection ofmethane, sodium carbonate as precipitating agent and polyethylene glycol (PEG) as antiagglomerationagent. The samples were characterized by X-ray diffraction (XRD), sorptionof N2 (BET method) and transmission electron microscopy (TEM). The XRD patterns showedthat the crystalline structure of starting iron oxide has not been affected by the introduction ofPt as doping material. All the sensors depicted micro-mesoporous isotherms correspondingto type IV. TEM micrographs showed the average particle size of samples, ranging from 50to 150 nm. Sensor tests were performed in a range of concentrations from 300 to 900 ppmand operation temperatures between 150 and 400 ºC. The sensor with 0,3% of Pt and 0,3%of PEG (20000) presented the highest gas response at 300ºC with an initial concentration of900 ppm of methane probably due to the well-defined hematite crystalline structure, gooddispersion of nanoparticles and the best contact surface over Pt surface.